The implementation of mini-research project to train undergraduate students’ scientific writing and communication skills - Agus Haryono; Chaidir Adam (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Scientific writing and communication skills of undergraduate students in the Biology Education Program of University of Palangka Raya need to be improved. The purpose of this research was to implement mini-research in animal ecology field practice to train undergraduate students’ scientific writing and communication skills. This descriptive quantitative research used action-research method with two cycles in which each cycle consisted of four stages i.e (1) plan; (2) take action; (3) collect and analyze evidences, and (4) reflect. The data gained were analyzed descriptively and quantitatively. The results showed that the gain score of students’ scientific writing skills based on mini-research assessment was 0.6 (moderate category). Moreover, students' communication skills showed an improvement from cycle 1 to cycle 2 which was assessed during the presentation session. All the findings in this study indicate that the implementation of the mini-research project in the field practice of the animal ecology course helps students to develop scientific writing and communication skills.